2006
DOI: 10.1007/s10592-005-9067-8
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography and Pleistocene demographic history of the endangered marsh deer (Blastocerus dichotomus) from the Río de la Plata Basin

Abstract: The marsh deer is the largest neotropical cervid with morphological and ecological adaptations to wetlands and riparian habitats. Historically, this now endangered species occupied habitats along the major river basins in South America, ranging from southern Amazonia into northern Argentina to the Parana´river delta. This particularly close association with wetlands makes marsh deer an excellent species for studying the effects of Pleistocene climatic changes on their demographic and phylogeographic patterns. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 40 publications
3
28
0
3
Order By: Relevance
“…Our expansion time estimates suggest that the studied species may have been exploring the area before the Holocene period, following an increase in moisture between 32,000 and 20,000 years ago in central Brazil (Ledru, 1993;SalgadoLaboriau et al, 1997). Our data are also in concordance with the pattern of demographic expansion reported for a species with similar habitat requirements, the marsh deer (Blastocerus dichotomus Illiger, 1815), in the same period and region (Marquez et al, 2006).…”
Section: Conservation Implicationssupporting
confidence: 90%
See 1 more Smart Citation
“…Our expansion time estimates suggest that the studied species may have been exploring the area before the Holocene period, following an increase in moisture between 32,000 and 20,000 years ago in central Brazil (Ledru, 1993;SalgadoLaboriau et al, 1997). Our data are also in concordance with the pattern of demographic expansion reported for a species with similar habitat requirements, the marsh deer (Blastocerus dichotomus Illiger, 1815), in the same period and region (Marquez et al, 2006).…”
Section: Conservation Implicationssupporting
confidence: 90%
“…Clapperton (1993) proposed that the Pantanal region exhibited an arid climate during the last glacial period (25,000-15,000 ybp). More recent studies performed in areas near the Pantanal have identified a much humid weather than the previously suggested (de Oliveira, 1992;Ledru, 1993;Ferraz-Vicentini and Salgado-Laboriau, 1996;Assine and Soares, 2004). Our expansion time estimates suggest that the studied species may have been exploring the area before the Holocene period, following an increase in moisture between 32,000 and 20,000 years ago in central Brazil (Ledru, 1993;SalgadoLaboriau et al, 1997).…”
Section: Conservation Implicationssupporting
confidence: 57%
“…The mitochondrial DNA (mtDNA) control region has been extensively used in conservation studies of many species of vertebrates (Eizirik et al, 1998;Möller et al, 2001;Montoya-Burgos, 2003;Cantanhede et al, 2005;Márquez et al, 2006;Barnett et al, 2006;Tchaicka et al, 2007). Due to the high polymorphism on its 5' end in vertebrates (Avise, 1994;Taberlet, 1996), this segment has been widely used in populational studies of mustelids such as Gulo gulo (Wilson et al, 2000;Chappell et al, 2004), Mustela putorius (Davison et al, 2000), Martes foina (Davison et al, 2001), Enhydra lutris (Larson et al, 2002), and Lutra lutra (Mucci et al, 1999;Cassens et al, 2000;Pérez-Haro et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Studies conducted in some Neotropical deer using this region as genetic marker, as in the pampas deer and the gray brocket deer, showed that this is very polymorphic and informative (González et al, 1998;Bidegaray et al, 2003). But in other species as the huemul and the marsh deer it showed discrete variation, being informative to conduct phylogeographic studies (Jara et al, 2005;Márquez et al, 2006).…”
Section: Genetic Variationmentioning
confidence: 99%
“…The use of microsatellites to estimate population size can be based on: Capture Mark Recapture method (Seber, 1982) and rarefaction analysis (Kohn et al, 1999). Few studies have compared genetic estimation with field data estimations to test reliability and accuracy only in bear (Belleiman et al, 2005) not yet in neotropical mammals.…”
Section: Population Estimationmentioning
confidence: 99%